2015
DOI: 10.1038/ejhg.2015.26
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the MED13L syndrome

Abstract: Congenital cardiac and neurodevelopmental deficits have been recently linked to the mediator complex subunit 13-like protein MED13L, a subunit of the CDK8-associated mediator complex that functions in transcriptional regulation through DNA-binding transcription factors and RNA polymerase II. Heterozygous MED13L variants cause transposition of the great arteries and intellectual disability (ID). Here, we report eight patients with predominantly novel MED13L variants who lack such complex congenital heart malfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 34 publications
4
72
0
1
Order By: Relevance
“…Our results support the findings reported by Adegbola et al (17) regarding the absence of congenital heart disease Gly2040Asnfs*32 (14) Gln1984Alafs*31 (17) (17) (17) Based exclusively on the clinical features, patients with mutations in the MED12 gene were previously classified in three different clinical syndromes, although all of them share in common, to a greater or lesser degree, the same clinical findings: somatic growth disorders (affecting weight and/or height), altered size of the head, micrognathia, philtrum anomalies, some dysmorphic facial features, genitourinary anomalies, abnormal hands and feet, in addition to problems in the central nervous system (agenesis of corpus callosum, seizures, autistic and/or hyperactive behavior, intellectual disability and developmental delay) (reviewed in refs. (11,18,19)).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results support the findings reported by Adegbola et al (17) regarding the absence of congenital heart disease Gly2040Asnfs*32 (14) Gln1984Alafs*31 (17) (17) (17) Based exclusively on the clinical features, patients with mutations in the MED12 gene were previously classified in three different clinical syndromes, although all of them share in common, to a greater or lesser degree, the same clinical findings: somatic growth disorders (affecting weight and/or height), altered size of the head, micrognathia, philtrum anomalies, some dysmorphic facial features, genitourinary anomalies, abnormal hands and feet, in addition to problems in the central nervous system (agenesis of corpus callosum, seizures, autistic and/or hyperactive behavior, intellectual disability and developmental delay) (reviewed in refs. (11,18,19)).…”
Section: Discussionsupporting
confidence: 83%
“…(11,18,19)). A very similar scenery has been found among the patients with mutations in the MED13L gene, who present a wide phenotypic spectrum which basically includes the same clinical features found in association to mutations in the MED12 (13,17,20,21).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, based on the most recent summary of DEAF1 patients, these patients have a more severe motor delay, severe delay in expressive speech (absent speech to ten single words), and very severe intellectual disability compared with our patient . Closer examination of the MED13L haploinsufficiency syndrome phenotype, through analyzing the 21 known reported MED13L variant cases , showed that our patient is similar to other MED13L haploinsufficiency cases (Table ). Further, similar missense mutations of MED13L that occur later in the protein in the C‐terminal region have a milder phenotype in terms of ID and language development .…”
Section: Resultssupporting
confidence: 58%
“…Comparing the phenotype of our patient to the core phenotypes of MED13L haploinsufficiency syndrome and DEAF1 ‐associated syndrome, it was apparent that both of these syndromes could fit with our patient's phenotype (Fig. ).…”
Section: Resultsmentioning
confidence: 85%